The impact of cancer and quality of life for post-treatment non-Hodgkin lymphoma survivors - Smith, Sophia K. (2010)
OBJECTIVE: Recent work suggests that perceptions of the impact of cancer on survivors’ lives are associated with physical and mental health and quality of life (QOL) outcomes. This study examines the association between the Impact of Cancer version 2 scales (IOCv2) and these outcomes in a large sample of survivors of adult non-Hodgkin lymphoma (NHL). METHODS: Participants completed a mailed survey to assess physical and mental health (SF-36), cancer-specific quality of life (FACT-G) and perceived impact of cancer (IOCv2). Hierarchical multiple regression models, in which demographic, clinical, psychosocial and IOCv2 measures were added sequentially, were employed to evaluate their contribution to explaining variance in SF-36 and FACT-G scores. RESULTS: A total of 652 post-treatment NHL survivors participated. Survivors with comorbidities and negative appraisals of life threat and treatment intensity reported worse physical and mental health and QOL (all P<.05). After controlling for demographic and clinical characteristics, younger respondents reported better physical but worse mental health and QOL (all P<.01). Lower IOCv2 Negative Impact (all P<.001) and higher Positive Impact (all P<.05) scores were associated with better physical and mental health and QOL after controlling for demographic, clinical and psychosocial characteristics. CONCLUSIONS: Findings suggest that perceptions of cancer’s impact on survivors’ lives may influence or be influenced by health status and functioning and QOL. Longitudinal research is needed to establish causality, which could lead to the development of interventions targeting survivors’ impact of cancer concerns, and ultimately to the enhancement of overall health and QOL.